RESTORATION OF PARTS OF AGRICULTURAL MACHINES WITH ZINC-BASED GALVANIC COATINGS - BRATSLAVETS, Bogdan (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Galvanizing is most often used to protect against corrosion. In repair production zinc coverings are used for protection against corrosion of fastening details and restoration of landing surfaces of lightly loaded details. Electroplating is the process of applying metal to the surface of parts by crystallizing it from an aqueous solution of the corresponding salts (electrolyte) when a direct current passes through them. An electrical circuit is closed by an electrolyte between two conductors called electrodes. The electrode to which the conductor of the external circuit with a plus is attached is called the anode, and with a minus - the cathode. The repaired part, on which the metal is built up, serves as the cathode, and the anode - plates, copper, lead, zinc, cadmium and other metals. In electrolysis, soluble and insoluble anodes are used. In practice, soluble lead is most often used, and insoluble lead is used only for chromium plating. The preparation of the surface of the part before coating (machining, degreasing, digestion) is important for the quality of the coating. The paper identifies the advantages and disadvantages of the method of updating parts of agricultural machinery with galvinic coatings based on zinc. This makes it possible to analyze the results of experiments and evaluate the effectiveness of using this method of restoring parts. The article presents the technological process of restoration of parts by galvinic galvanizing using an activator and the results of experiments using graphs of the dependence of the rate of coating on the current density and the speed of the activator. Determine whether the use of an experimental activator will increase the speed and quality of coating on parts.